Entrepreneurship - Hisrich, Robert D.; Peters, Michael P.; Shepherd, Dean A. (McGraw-Hill, 2024)
The 12th edition of Entrepreneurship provides an understanding of the people and processes that create and grow new ventures on an international basis. It focuses on the risk and effort of creating something new and overcoming inertia through each of its five major sections: The Entrepreneurial Perspective, From the Idea to the Opportunity, From the Opportunity to the Business Plan, From the Business Plan to Funding the Venture, and From Funding the Venture to Launching, Growing and Ending the New Venture. Each chapter begins with learning objectives and a profile of an entrepreneur whose career is especially relevant to the chapter material. Numerous business examples occur throughout each chapter along with important websites to assist the reader in getting started. Boxed summaries of articles in the news (As Seen in Business News) illustrate the chapter discussions and Ethics boxes discussing ethical issues are found in all the chapters. Each chapter concludes with research tasks, class discussion questions, and selected readings for further research and study. At the end of the book is a selection of Cases that can be used along with any chapter, as well as listing of other appropriate cases on a chapter-by-chapter basis.